The potent and selective α4β2*/α6*‐nicotinic acetylcholine receptor partial agonist 2‐[5‐[5‐((S)Azetidin‐2‐ylmethoxy)‐3‐pyridinyl]‐3‐isoxazolyl]ethanol demonstrates antidepressive‐like behavior in animal models and a favorable ADME‐tox profile. Issue 2 (12th March 2014) - Yu, Li‐Fang; Brek Eaton, J.; Zhang, Han‐Kun; Sabath, Emily; Hanania, Taleen; Li, Guan‐Nan; van, Richard B.; Whiteaker, Paul; Liu, Qiang; Wu, Jie; Chang, Yong‐Chang; Lukas, Ronald J.; et al.
Abstract Preclinical and clinical studies demonstrated that the inhibition of cholinergic supersensitivity through nicotinic antagonists and partial agonists can be used successfully to treat depressed patients, especially those who are poor responders to selective serotonin reuptake inhibitors (SSRIs). In our effort to develop novel antidepressant drugs, LF‐3‐88 was identified as a potent nicotinic acetylcholine receptor (nAChR) partial agonist with subnanomolar to nanomolar affinities for β2‐containing nAChRs (α2β2, α3β2, α4β2, and α4β2*) and superior selectivity away from α3β4 − (Ki > 104 nmol/L) and α7‐nAChRs (Ki > 104 nmol/L) as well as 51 other central nervous system (CNS)‐related neurotransmitter receptors and transporters. Functional activities at different nAChR subtypes were characterized utilizing 86Rb+ ion efflux assays, two‐electrode voltage‐clamp (TEVC) recording in oocytes, and whole‐cell current recording measurements. In mouse models, administration of LF‐3‐88 resulted in antidepressive‐like behavioral signatures 15 min post injection in the SmartCube® test (5 and 10 mg/kg, i.p.; about 45‐min session), decreased immobility in the forced swim test (1–3 mg/kg, i.p.; 1–10 mg/kg, p.o.; 30 min pretreatment, 6‐min trial), and decreased latency to approach food in the novelty‐suppressed feeding test after 29 days chronic administration once daily (5 mg/kg but not 10 mg/kg, p.o.; 15‐min trial). In addition, LF‐3‐88 exhibited a favorable profile in pharmacokinetic/ADME‐Tox (absorption, distribution, metabolism, excretion, and toxicity) assays. This compound was also shown to cause no mortality in wild‐type Balb/CJ mice when tested at 300 mg/kg. These results further support the potential of potent and selective nicotinic partial agonists for use in the treatment of depression.